KEBIJAKAN PERLINDUNGAN HUKUM TERHADAP GURUDARI UPAYA KRIMINALISASI GURUDALAM DUNIA PENDIDIKAN - Putra, Dharma Yuda; Artina, Dessy; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In the sense that education is often interpreted as a human effort to foster his personality inaccordance with the valuesin societyand culture. The educational process carried out and carried out by anation, in an effort to foster and develop national character or personality, advance the life of the nation invarious fields of life, and achieve the national goals concerned is what is called the national educationsystem which usually grows and develops from the history of the nation concerned, which is influenced byvarious factors and resources as well as the potential that exists in the nation besides the external factors, ofcourse, but the problem that currently often occurs and becomes an unresolved problem is thecriminalization of teachers. Where the teacher must deal with the law if giving sanctions to students whomake mistakes. Even though the sanction given by the teacher has been regulated in GovernmentRegulation Number 74 of 2008 concerning Teachers. This regulation was followed up by Law No. 14 of2005 concerning Teachers and Lecturers. Based on this understanding, the writer of this thesis formulatestwo formulations of the problem, namely: first, what is the legal protection policy for teachers from theattempt to criminalize teachers in the world of education. Second, how is the ideal concept to overcome thecriminalization of teachers in carrying out the educational process.This type of research can be classified in normative juridical research, because this research isconducted by examining secondary data and approaches to law, this normative study examines the legalprinciples of reasons that can eliminate criminal. The data sources used are, primary data, secondary data,tertiary data, data collection techniques in this study are normative juridical, the data used is libraryresearch.In the results of the problem research there are two main things that can be concluded. First, thelegal protection policy for teachers has been regulated in the Law, but the course of the rule of law is stillproblematic with the cases that the authors explain. The second needs a review of the Child Protection ActArticle 35 of 2014, which states that children get protection from acts of violence in the world of education.Where protection from acts of violence that can get protection, because if left unchecked it will have anegative impact on both the teacher in educating and students as students.Keywords: Criminalization, Reasons for the Elimination of Criminal Procedure, Legal Policy, LegalProtection